2015
DOI: 10.1016/j.jacc.2014.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Complete Versus Lesion-Only Revascularization in Patients Undergoing Primary Percutaneous Coronary Intervention for STEMI and Multivessel Disease

Abstract: BackgroundThe optimal management of patients found to have multivessel disease while undergoing primary percutaneous coronary intervention (P-PCI) for ST-segment elevation myocardial infarction is uncertain.ObjectivesCvLPRIT (Complete versus Lesion-only Primary PCI trial) is a U.K. open-label randomized study comparing complete revascularization at index admission with treatment of the infarct-related artery (IRA) only.MethodsAfter they provided verbal assent and underwent coronary angiography, 296 patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
393
4
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 713 publications
(458 citation statements)
references
References 20 publications
20
393
4
8
Order By: Relevance
“…In contrast, as in the present study, Shacham and colleagues could not find an independent association between V/eGFR and AKI 22. Furthermore, in randomized trials of complete versus lesion‐only revascularization in patients undergoing pPCI, contrast volume was higher in the multivessel‐PCI group with similar CI‐AKI rates 24, 25. Recently, Kooiman reported that a high contrast dose (contrast volume [in ml] ≥3× baseline eGFR) was only a marginal predictor of AKI after PCI, with an estimated attributable risk fraction to AKI of 10.6% 14…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast, as in the present study, Shacham and colleagues could not find an independent association between V/eGFR and AKI 22. Furthermore, in randomized trials of complete versus lesion‐only revascularization in patients undergoing pPCI, contrast volume was higher in the multivessel‐PCI group with similar CI‐AKI rates 24, 25. Recently, Kooiman reported that a high contrast dose (contrast volume [in ml] ≥3× baseline eGFR) was only a marginal predictor of AKI after PCI, with an estimated attributable risk fraction to AKI of 10.6% 14…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, the better outcomes seen in the angiographic CR group were similarly observed in various subgroups, especially in patients with younger age (<65 years), acute coronary syndrome, and left ventricular dysfunction. These results are also in line with previous studies that evaluated the prognostic implication of angiographic CR in patients with acute ST‐segment elevation MI or left ventricular dysfunction 23, 24, 25…”
Section: Discussionsupporting
confidence: 92%
“…The study design and main results were published previously 8, 9. CvLPRIT‐CMR was a prespecified substudy of a multicenter, prospective, randomized, controlled, open‐label, clinical trial8 with blinded CMR end point analysis conducted at 7 UK centers between May 2011 and May 2014.…”
Section: Methodsmentioning
confidence: 99%